Synthesis and characterization of cycloamino and oxime-linear phosphazenes - Baran, H.; Cil, E.; Arslan, M. (Maik Nauka/Interperiodica/Springer, 2007)
The reactions of N-dichlorophosphoryl-P-trichlorophosphazene, Cl3P=N-P(O)Cl-2, with 1-methylpiperazine, 1-benzylpiperazine, 4-methylpiperidine, 2-methylpiperidine, 4-hydroxybenzaldehyde, and hydroxylaminehydrochloride were studied. Experimental studies were carried out in argon atmosphere. Pentaaminophosphazenes were obtained from 1-methylpiperazine and 1-benzylpiperazine. Phosphinoyl compounds formed from 4-methylpiperidine and 2-methylpiperidine. Phosphoryl compound was obtained from 4-hydroxybenzaldehyde. Oxime derivative of tris(4-formylphenoxy) phosphoryl was prepared from hydroxylamine hydrochloride.
Keywords: monophosphazenes; phosphinimines; Amine-substituted monophosphazenes; aminolysis; oximelinear phosphazenes